Barriers to pond fish culture entrepreneurship in Tripura: An empirical study - PANDEY, D K; DE, H K; PATEL, A B; UPADHYAY, A D (The Indian Journal of Animal Sciences, 2015)
The study on pond fish culture entrepreneurship was undertaken in Tripura through survey among 240 fish farmers. Seven attributes, viz. innovativeness, farm decision making, achievement motivation, knowledge of farming enterprises, risk taking ability, leadership ability and cosmopolitan nature were measured to study the overall entrepreneurial attribute of the fish farmers. Around 69% of the respondents have medium level of entrepreneurship and over 85% possess medium level of aspiration. Among the socio-economic and infrastructural factors that hinder entrepreneurship were lack of technical know-how on pond management, low level of education, social norms and beliefs, marketing and financial problems, poor transportation and storage facilities. The authors argue for creation of enabling infrastructure to promote entrepreneurship in pond fish culture.